PERANAN BUDAYA ORGANISASI BERBASIS MINDFULNESS DALAM MEMEDIASI PENGARUH KEPEMIMPINAN DIGITAL TERHADAP PRODUKTIVITAS GURU: Indonesia - Juni Suryanadi; Susanto Susanto; Khairudin Khairudin (STKIP Pesisir Selatan, 2026)
Objective: Implementing effective digital leadership in schools is essential for advancing digital technology and boosting teacher productivity. This research investigates how digital leadership influences teacher productivity directly and indirectly via a mindfulness-oriented organizational culture, within schools of the Ekayana Education Group Jakarta. Using a quantitative, causal‑associative design, the study surveyed 41 teachers, gathering data through questionnaires and analyzing it with Partial Least Squares–Structural Equation Modeling (PLS‑SEM). Findings reveal that digital leadership positively and significantly impacts both teacher productivity and mindfulness‑based organizational culture. Additionally, a mindfulness‑focused organizational culture positively affects teacher productivity and serves as a significant mediator between digital leadership and teacher productivity. These results underscore that enhancing digital leadership, supported by a mindfulness‑based organizational culture, is an effective approach for sustainably elevating teacher productivity.